2015
DOI: 10.1016/j.jpainsymman.2014.11.293
|View full text |Cite
|
Sign up to set email alerts
|

Advance Care Planning Does Not Adversely Affect Hope or Anxiety Among Patients With Advanced Cancer

Abstract: Engaging in ACP with online planning tools increases knowledge without diminishing hope, increasing hopelessness, or inducing anxiety in patients with advanced cancer. Physicians need not avoid ACP out of concern for adversely affecting patients' psychological well-being.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
102
1
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 108 publications
(119 citation statements)
references
References 52 publications
5
102
1
7
Order By: Relevance
“…The finding of present research indicated that mindfulness-based cognition therapy was effective on suicidal thoughts and death anxiety in patients with cancer. The findings of this research were consistent with the results of Walker et al [6], Green and Walker [26], Carlson [28], Kabat Zinn [29], Carlson and Garland [30], Martin [31], Salajegheh and Raghibi [32], Sullivan et al [33], Nyklicek and Karlijn [34].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The finding of present research indicated that mindfulness-based cognition therapy was effective on suicidal thoughts and death anxiety in patients with cancer. The findings of this research were consistent with the results of Walker et al [6], Green and Walker [26], Carlson [28], Kabat Zinn [29], Carlson and Garland [30], Martin [31], Salajegheh and Raghibi [32], Sullivan et al [33], Nyklicek and Karlijn [34].…”
Section: Discussionsupporting
confidence: 91%
“…The findings related to this hypothesis were consistent with the results of Mousavi [24], Kaviani et al [16], Walker et al [6], Forkman et al [25], Green and Walker [26], Kim [27], Carlson [28], Kabat Zinn [29], Carlson and Garland [30], and Martin [31]. In order to explain these findings, we can say that cancer is associated with negative thoughts, especially thoughts of suicide.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Consistent with previous studies involving other patient populations, we found that after using the decision aid, patients’ knowledge of ACP increased, and patients expressed high levels of satisfaction with MYWK (37, 40, 42, 49, 50). So too, there were no adverse effects on anxiety, which should help allay concerns some clinicians have about discussing end-of-life issues with patients.…”
Section: Discussionsupporting
confidence: 90%
“…Baseline measures included: 1) Demographics and Health Assessment (22 items); 2) Self-Determination (8 items, adapted from Pellino (41), assessing individuals’ sense of control over future treatments); 3) Advance Care Planning Knowledge (27 items, previously described (42), assessing knowledge of the advance care planning process and the clinical decisions patients often face at the end of life); 4) Anxiety (State Trait Anxiety Inventory (43)); 5) Functional Status (ALS Functional Rating Scale-Revised ALSFRS-R (44)); and 6) Quality of Life (ALS-Specific QoL Scale (45)).…”
Section: Methodsmentioning
confidence: 99%